Am I doing the right thing? Unpacking workplace rituals as mechanisms for strong organizational culture. (October 2016) - Erhardt, Niclas; Martin-Rios, Carlos; Heckscher, Charles
Abstract: Workplace rituals are powerful learning mechanisms for core values that underpin organizational culture in restaurants. Yet, more research is needed to identify different types and how these rituals operate to reinforce core values in different organizational cultures. Drawing on ritual theory, organizational culture and hospitality research, we use 52 semi-structured interviews and 20 observations to study four restaurants representing clan, ad hoc, market, and hierarchy cultures. We identify and unpack eight employee-focused emotional, behavioral, and cognitive workplace rituals linked with owners' core values such as comradery, creativity, competition and efficiency. Finally, we discuss practical implications of workplace rituals as they relate to business identity, selection, retention and day-to-day management of employees to further strengthen said culture.